Inventory control using maximo series 5 basic school software / Sabri Mohd Tahir, Marsuhaila Maaris and Shahizam Mohd Sharif - Mohd Tahir, Sabri; Maaris, Marsuhaila; Mohd Sharif, Shahizam (Faculty of Mechanical Engineering, 1998)
The term inventory is used in day to day life as manpower inventory, equipment inventory, inventory of documents, inventory of raw materials, inventory of spare parts, inventory of semi-finished items, inventory of finished goods and inventory of vehicles. The Longman Dictionary defines the word inventory as “stock of goods”. Inventory, in management parlance, is an idle resource of any kind having an economic value. So long as the resource is kept in the warehouse, it is idle. But, the material has economic value in the sense that it is capable of being converted to semifinished and finished goods and sold to the customers to buy more items. This kind of cycle goes on and on. Even though in practice the term covers only industrial items, this concept can be extended to other things, such as water, forests, space and manpower. For example, too much water causes flood and too little of it results in drought.